PROPAGATION OF LOCALLY ISOLATED BACILLUS THURINGIENSIS (CAMB 3-023) FOR THE PRODUCTION OF SPORE-CRYSTAL PROTEIN IN SHAKE FLASK - Zafar, A U; Riazuddin, S (Biological Sciences - PJSIR, 2002)
The shake flask cultural conditions were optimized for the production of spore/crystal protein by locally isolated Bacillus thuringiensis strai n CAME 3-023. Of all the culture media tested , Corn Steep liquor medium with the addition of MnS0 and CaC1 2 1 gave highly encouraging results of spore counts (l .8X108/ml), crystal protein yield (42 mg g· 4 dry mass) and also maximum dry cell mass (3.9 g t\ The final pH of the fermented mash was alkaline (9.0), 72 h after inoculation with vegetative cells.